Classification of emotions and evaluation of customer satisfaction from speech in real world acoustic environments - Parra-Gallego, Luis Felipe; Orozco-Arroyave, Juan Rafael (Digital Signal Processing, 2022)
This paper focuses on finding suitable features to robustly recognize emotions and evaluate customer satisfaction (CS) from speech in real acoustic scenarios. The classification of emotions is based on standard and well-known corpora and the evaluation of CS is based on recordings of real opinions given by customers about the received service during phone calls with call-center agents. The feature sets considered in this study include two speaker models, namely x-vectors and i-vectors, and also the well known feature set introduced in the Interspeech 2010 Paralinguistics Challenge (I2010PC). Additionally, we introduce the use of phonation, articulation and prosody features extracted with the DisVoice framework as alternative feature sets to robustly model emotions and CS from speech. The results indicate that the I2010PC feature set is the best approach to classify emotions in the standard databases typically used in the literature. When considering the recordings collected in the call-center, without any control over the acoustic conditions, the best results are those that include our articulation features. The I2010PC feature set includes 1584 measures while the articulation approach only includes 488 measures. We think that the proposed approach is more suitable for real-world applications where the acoustic conditions are not controlled and also it is potentially more convenient for industrial applications.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Automatic speech recognition; Customer satisfaction; Pattern recognition; Speech emotion recognition; Speech processing